‘A double-edged sword?’ Digital storytelling for early childhood education: Vietnamese teachers’ beliefs and practices - Le Ngoc Hoa; Lu Hung Minh (UIN Raden Mas Said Surakarta, 2022)
The advancement of Information Communication and Technology (ICT) offers enormous opportunities to enhance the efficacy of learning process in all levels of education, including Early Childhood Education (ECE). However, in the light of the recent years, there have not been some concern about the issue of use of technology to assist ECE process in the context of Vietnam. Thus, this study explores Vietnamese early childhood teachers’ beliefs and practices about the use of technology to facilitate storytelling for pre-school children. A web-based survey research was adopted to scrutinize the beliefs and practices of 228 ECE teachers about digital storytelling in Can Tho Vietnam. The results demonstrated that these teachers hold high levels of beliefs that digital storytelling could be used to enhance learning. In addition, they had carried out digital storytelling activities in their learning practices. The results emphasized that several concerns must be taken by teachers, parents, and related stakeholders in using technological tools in young children’s learning environment. This study offers pedagogical insights for ECE teachers to integrate digital storytelling in their learning activities. In short, the use of technology for pre-school children can provide a lot of benefits if it is skillfully executed by both teachers and parents.